Respuesta :

Lanuel

Answer:

1. 2268.

2. 12.

Step-by-step explanation:

1. Given the mathematical expression; 2 * 2 * 9 * 7 * 9

We would simplify the expression;

2 * 2 * 9 * 7 * 9 = 4 * 81 * 7

2 * 2 * 9 * 7 * 9 = 28 * 81

2 * 2 * 9 * 7 * 9 = 2268

2. Given the mathematical expression; 2² + 2 * 2²

From BODMAS (Bracket Of Division Multiplication Addition Substraction), we would first of all multiply before performing an addition operation.

Therefore,

2² + 2 * 2² = 4 + 2 * 4  

2² + 2 * 2² = 4 + 8

2² + 2 * 2² = 12

Answer:

1. 2268 2. 12

Step-by-step explanation:

ACCESS MORE